Produção de liteira fina em uma área de contato campinarana-floresta ombrófila na Amazônia Setentrional - Silva, Williamar Rodrigues (2013)
Annual production of fine litter was measured between February 2012 and February 2013 in a campinarana-terra-firme forest ecotonein Viruá National Park, Roraima. This study investigated the relationship between the monthly production of fine litter and monthly precipitation, and evaluated the effect of spatial variation in texture and soil fertility in the production of fine litter. The production of fine litter was monitored in 15 1-hectare permanent plots located in the grid of Brazilian Biodiversity Research Program (PPBio). Five 0. 25m2 litter collectors were installed in each plot and were monitored bimonthly. After collection, samples were dried at 60o C for 48 hours, separated into different fractions (leaves, branches thinner than 2 cm in diameter, flowers, fruits/seeds and materials not identified) and weighed. The total production of fine litter ranged from 5, 86 t /ha/year to 12, 10 t/ ha/ year with an average of 8, 83 t/ ha/ year. There were no significant differences between the annual production of fine litter in areas of terra-firme forest and campinarana. Most of the litter was composed of leaves which represented 66, 55% of the total, followed by twigs (21, 94%), fruits (6, 32%), flowers (2, 96%) and unidentified materials (2, 23%). Monthly production of fine litter was not correlated with monthly rainfall (rs = 0, 27, p = 0, 33). Only the production of fruits / seeds (rs = 0, 13, p = 0, 05), and branches (rs = 0, 20, p <0, 01) was correlated with precipitation. The spatial variation in litter production was not related to texture or soil fertility in the campinarana. Likewise, there was no relationship between the production of fine litter and texture in the terra-firme forest. However, there was a relationship between production and soil fertility (r² = 0, 39; p = 0, 05). Canopy openness affected the production of fine litter, but its effect was dependent on the vegetation type. In areas of terra-firme forest, the production was not related to canopy openness. On the other hand, in the campinarana production was directly related to canopy openness (r² = 0, 93; p = 0, 01).